Investigating urban traffic based noise pollution in the city of Kirikkale, Turkey - Akgüngör, Ali P.; Demirel, Abdulmuttalip (Transport, 2008)
The study presents an investigation into traffic based noise pollution in the city of Kirikkale, Turkey. For this purpose, traffic noise levels were measured at 15 intersections across the city during three peak times ‐ morning (08:00–09:00), noon (12:30–13:30) and evening (17:00–18:00) hours. The comparison of Leq values against the limit values of the Turkish Noise and Control Regulations for Settlement Zones showed that Leqvalues exceeded the limits at all stations. A linear regression analysis performed between the Leq and logarithm of total traffic volume (log Q) produced a coefficient of determination of 0.52. A multi regression analysis carried out between the Leq and four different vehicle types resulted in a correlation coefficient of 0.74. The correlation matrix indicated that the highest correlation was found for trucks/buses with r = 0.92. The spatial maps of traffic noise created by the Kriging method under ArcView GIS displayed that there seemed to be significant differences in the spatial variation of traffic noise across the city. In order to reduce traffic based noise levels within the city some useful suggestions were presented.First published online: 27 Oct 2010